2004
DOI: 10.1128/mcb.24.16.7091-7101.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Import by the Proapoptotic Protein CC3

Abstract: We report here that the normal cellular protein CC3/TIP30, when in excess, inhibits nuclear import in vitro and in vivo. CC3 binds directly to the karyopherins of the importin ␤ family in a RanGTP-insensitive manner and associates with nucleoporins in vivo. CC3 inhibits the nuclear import of proteins possessing either the classical nuclear localization signal or the M9 signal recognized by transportin. CC3 also inhibits nuclear translocation of transportin itself. Cells modified to express higher levels of CC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
83
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 54 publications
9
83
0
Order By: Relevance
“…Recent results have shown that CC3 can bind directly to karyopherins of the importin ␤ family of nuclear transportins in a Ran-GTP-insensitive manner (5). For importin ␤2, the site of interaction with CC3 involves HEAT domain(s) in the Cterminal third of the protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results have shown that CC3 can bind directly to karyopherins of the importin ␤ family of nuclear transportins in a Ran-GTP-insensitive manner (5). For importin ␤2, the site of interaction with CC3 involves HEAT domain(s) in the Cterminal third of the protein.…”
mentioning
confidence: 99%
“…Cells modified to overexpress CC3 have slower rates of nuclear transport and higher sensitivity to death signals. CC3 mutated in the region of a nucleotide binding motif (GXXGXXG, between residues 25 and 31) lacked apoptotic properties and had weakened interactions with importin ␤2 (5).…”
mentioning
confidence: 99%
“…On the other hand, inhibition of nuclear transport factors has been reported as a powerful apoptotic trigger after a study on protein CC3. The latter impairs the function of several nuclear import receptors, such as transportin, 4 and its overexpression predisposes tumour cells to apoptosis. 5 Similarly, the reduction of importin-b and importin-a3 levels leads to an increase in the number of apoptotic cells.…”
mentioning
confidence: 99%
“…TIP30, which exhibits decreased expression in some cancer cells NicAmhlaoibh and Shtivelman, 2001;Shtivelman, 1997;Tong et al, 2009;Zhao et al, 2006), is a tumor suppressor with proapoptotic activity (El Omari et al, 2005;Xiao et al, 2000;Zhao et al, 2007) as well as with anti-metastatic Shtivelman, 1997;Tong et al, 2009;Xiao et al, 2000;Zhao et al, 2007) and angiogenesis-inhibiting (NicAmhlaoibh and Shtivelman, 2001) properties. TIP30 binds importin-β, which facilitates the cytoplasm-to-nuclear transport of proteins (El Omari et al, 2005;King and Shtivelman, 2004;Zhao et al, 2008), including HuR (Guttinger et al, 2004;Wang et al, 2004). The cytoplasmic HuR enhances the UV irradiation-induced expression and transcriptional activity of the tumor suppressor p53 by binding to the 3′ untranslated region of its mRNA and enhancing its translation (Mazan-Mamczarz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Second, TIP30 may act as a regulator of importin activity. It is known that TIP30 interacts with importin (El Omari et al, 2005;King and Shtivelman, 2004;Zhao et al, 2008) and importins have been shown to translocate p53 protein across the nuclear membrane by interacting with the NLS of p53 (Komlodi-Pasztor et al, 2009;Li et al, 2007). Since TIP30 protein interacts with both importin and p53, we can envision a complex in which TIP30 acts as a bridge between p53 and importin, facilitating nuclear translocation of p53.…”
mentioning
confidence: 98%